HISTÓRIA, REGIÃO E ESPACIALIDADE (Revista de História Regional, 2007)
This article attempts to clarify and discuss the relations between space and History. The emphasis is in the various historiographic modalities of History for which ones the concepts of space, region, and territoriality have a significant centrality. The Regional History, the Geo-History, and the interdisciplinary relations between History and Geography are specially emphasized.